(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
The article studied and analyzed the influence of bentonite clay standards and irrigation regime on the weight of 1000 grains of winter wheat varieties in light gray soils of the Kashkadara region. When analyzing, the soil moisture before irrigation was 75-80-70% NH in irrigated options, seeds of winter wheat varieties «Shukrona» and «Turon» 40; 50 kg/t of bentonite clay when used, the weight of 1000 grains is 42 and 52 g, will ensure the cultivation of high-quality grain crops.